ANALISIS PENGGUNAAN ALAT EARTH TESTER UNTUK MENENTUKAN NILAI GROUNDING DI PERUSAHAAN UMUM PENYELENGGARA PELAYANAN NAVIGASI PENERBANGAN INDONESIA (PERUM LPPNPI) CABANG DENPASAR - Budi Prakasa Ramadhani; Dian Budhi Santoso (Peneliti.net, 2023)
Grounding or grounding is a very important thing in the electrical world because with this grounding or grounding by reducing the risk of accidents caused by leakage of electric current that can occur. Not only that, by doing grounding or grounding, it can minimize or reduce damage to electronic devices in a building. This study aims to determine the comparison of grounding values between the DVOR building and the MPH building at PERUM LPPNPI by analyzing the use of earth tester tools to determine the grounding value.